Pengaruh Pendidikan Paud Terhadap Tingkat Perkembangan Anak Usia Toodler Di Paud Diponegoro Dsn. Pucanganom Ds. Sukorejo Kec. Gurah Kab. Kediri - Susi Erna Wati; Siti Aizah (Akademi Keperawatan Dharma Husada Kediri, 2016)
Child development is the increased ability of the structure and function of the body is more complex. 48% of Indonesian children experiencing delays in development. The quality of child development is influenced by several factors, one of which is a stimulation or education. The method used is comparative analytic with cross sectional approach. The population is all children age (1-3 years) .In RW 05 Dsn. Pucanganom Ds. Sukorejo by 41 children. The sample was selected at the time the respondent was at the time of the study a number of 26 children Collecting data using KPSP sheet. Data were analyzed using Mann Whitney U-Test. The results showed that almost all (80%) of children who attend early childhood development that are tailored and most (62.5%) of children who do not follow early childhood development that are dubious. After doing the calculation using the Mann Whitney U-Test values ​​obtained significant asymetri 0,017. So we can conclude there is a difference between the development of children who attend early childhood education and do not follow the Early Childhood Education. Recommendations from this study is expected to hold a health officer introduction of the Early Childhood Education program for the improvement of child development at the Posyandu, polindes and other community activities. Keywords: early childhood education, child development